Gadget usage trends: How parental rules are prominent to us? - Hon Kai Yee; Crystal Ling; Chua Bee Seok; Yap Chin Choo; Gan Su Wan (Fakulti Psikologi dan Pendidikan, 2021)
Being born into the digital world, Malaysian children and adolescents are exposed to and immersed with various gadget usage. However, there are still limited research base as to how the gadget usage predominant the pre-adolescents’ life in Malaysian context from the rural and urban perspectives. In the pre-adolescence stage, they tend to associate their environment with personal and relational changes. The gadgets enable them to explore their building identities and sense of belonging on a greater scale. However, with the gadget integrated interaction, it may conflict with the parental rules about screen time and gadget usage control. There should be an effective strategy as to how the parents mediate the children’s usage of gadgets on the daily basis. The aims of the study include: (1) To understand the nature of gadget usage among rural and urban 9-to-11-year-olds. (2) To figure out the parental rules in term of disclosure and comment as well as conditional constraints. 385 children from rural and urban primary schools (3rd to 5th grade) in Sabah participated in the survey with the questionnaires related to the nature of gadget usage and parental rules. From the results, majority of the children preferred using smartphones for games/entertainments. Their behaviors exhibited prolonged time spent on gadgets and lack of physical activities. There are still lack of awareness in parental rules related with disclosure and comment disclosure (especially in identity and personal information safety) as well as conditional constraints (especially after bedtime and in a certain social context) among the children. In conclusion, it is perceptible that self-control and effective enforcement of parental rules still need to be addressed. It is important to moderate the parents’ authority and control over the children’s gadget usage and encourage the children to practice healthy gadget use behavior.